Blood rubies - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries., 2014)
"Ana Yartsin is on the verge of becoming a celebrity chef. Her custom Faberge egg-shaped cakes have brought her national attention, as has the story behind the cakes: her family owns the spectacular Faberge spring egg snow globe, a magnificent example of the master craftsman's work that includes five ruby-red tulips. As she prepares to be filmed for a reality TV show about the launch of her bakery in Rocky Point, New Hampshire, Ana hires antiques expert Josie Prescott to appraise the precious egg and snow globe ... When Josie arrives at Ana's home, however, she finds [someone] murdered and the priceless snow globe smashed beyond repair"--